Did the NFL lockout expose the Achilles heel of competitive sports? - Myer, G. D.; Faigenbaum, A. D.; Cherny, C. E.; Heidt Jr., R. S.; Hewett, T. E. (Journal of Orthopaedic & Sports Physical Therapy, 2011)
Over the past few months we have been afforded a unique opportunity to evaluate injury rate data prior to, during, and following the historical aberration created by the recent National Football League (NFL) Lockout. During this period (March 11th to July 25th, 2011), professional football players underwent an uncommon offseason, without the normal access to their team`s healthcare providers, strength and conditioning professionals, and high-level coaches. With limited access to these professionals and an absence of the structured preseason preparatory conditioning normally progressed over a 14-week period between May and July, we had a unique window of opportunity to evaluate the effects of an alarmingly rapid transition from the start of training camp, which took place 2 days after the end of the Lockout, to the initiation of preseason competition. A glimpse at early data, limited to Achilles tendon injuries, is cause for concern due to an unprecedented number of Achilles tendon ruptures in training camp and the beginning of preseason. Volltext: http://wellingtonortho.com/wp-content/uploads/October2011-GuestEditorial-Myer_1.pdf